Erfahrungen aus der Programmkommission für die VHB-Pfingsttagung 2018 - Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2018)
Die Bildung und Arbeit der Programmkommission für die VHB-Pfingsttagung 2018 in Magdeburg wird beschrieben. Erstmals wird dazu ein Sonderheft der Verbandszeitschrift Business Research erscheinen. – – The formation and work of the programme committee for the VHB (German Academic Association for Business Research) Annual Conference 2018 in Magdeburg is described. For the first time, an accompanying special issue of the association's journal Business Research will be published.
Keywords: I23; L31; L86; M00; 650